DOI: 10.30955/gnc2019.00201
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Rare Earth Elements in Waste Printed Circuit Boards (WPCBs) and their bioleaching potential

Abstract: Printed circuit boards (PCBs) are part of everyday items such as cellular phones and computers, and they constitute a significant proportion of e-waste. PCBs contain hazardous components but also valuable and critical materials such as copper, gold, silver and rare earth elements. Rare earth elements (REE) are crucial to modern hardware and due to their increasing demand and high supply risk, they are now considered to be amongst the most critical elements in the world. In this research, WPCBs were supplied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…The differences in the metal content at different PS are associated with heterogeneity of PCB samples themselves [14]. The Al composition varied within the PS, and it was mostly deposited at PS ranging from 38 to 150 µm and similar results were observed by Gonzalez-Baez et al [21] when the authors characterized the PCB at different PS (<500 µm, 500-1000 µm, 1000-2000 µ, and >2000 µm). A study by Priya and Hait [6] is in agreement with the findings of this study where the authors evaluated the metal content of TV PCB at different PS (38-75 µm, 75-180 µm, 180-250 µm, 250-500 µm, 500-1000 µm, and >1000 µm) and their study revealed that base metals such as Cu, Zn, Al, Pb, and Mn were the highest at PS of 75-180 µm [6].…”
Section: Printed Circuit Board Elemental Compositionmentioning
confidence: 55%
See 1 more Smart Citation
“…The differences in the metal content at different PS are associated with heterogeneity of PCB samples themselves [14]. The Al composition varied within the PS, and it was mostly deposited at PS ranging from 38 to 150 µm and similar results were observed by Gonzalez-Baez et al [21] when the authors characterized the PCB at different PS (<500 µm, 500-1000 µm, 1000-2000 µ, and >2000 µm). A study by Priya and Hait [6] is in agreement with the findings of this study where the authors evaluated the metal content of TV PCB at different PS (38-75 µm, 75-180 µm, 180-250 µm, 250-500 µm, 500-1000 µm, and >1000 µm) and their study revealed that base metals such as Cu, Zn, Al, Pb, and Mn were the highest at PS of 75-180 µm [6].…”
Section: Printed Circuit Board Elemental Compositionmentioning
confidence: 55%
“…This finding agrees with the results observed by Veit et al [20] where the authors revealed that Cu, Pb, and Sn were more embedded in the coarser fraction of the PCBs. A study by Gonzalez-Baez et al [21] observed that Cu and Sn content increased with the increase in PS whereas Benzal [14] observed that the Cu content in a different PS (200-1000 µm, 1000-3000 µm, 5000 µm, and 10,000 µm) decreased with an increase in PS and the highest Cu content achieved was 39 wt.% at PS of 200-1000 µm. Another study [22] disagrees with the findings of the present study, about Cu, when characterizing the metal content at different PS (<365, 35-500, and 500-750 µm), they found that Cu was highly embedded at the lowest PS of <365 µm, which was 62.1 wt.% and the metal content decreased with the increase in the PS.…”
Section: Printed Circuit Board Elemental Compositionmentioning
confidence: 99%
“…. ) [1] or metals like tantalum, cobalt, or nickel, which are fundamental components of many electronic devices [2]. Such metals and materials have therefore been identified as critical raw materials [3].…”
Section: Background On E-waste Challengesmentioning
confidence: 99%
“…For the components to be sorted, they first need to be dismantled from the PCBs through a disassembly process. Various industrial or pre-industrial methods are already available for this disassembly, either chemical, by dissolving solder joints using acids, by solder fusion, or by simple mechanical means [1]. These methods all have advantages and drawbacks depending on what constraints are applied to the components, sometimes burning them, corroding them, or possibly breaking them.…”
Section: Advanced Sorting Technicsmentioning
confidence: 99%